Representasi Nilai Toleransi dalam Animasi Keluarga Somat Episode “Hari Kartini” - Budi Santoso; Irma Winingsih (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2022)
This study aims to describe representation of the value of tolerance in the animation film Somat’s Family episode